Abstract Number ‐ 131: Microsurgical Clipping and Endovascular Treatment of Paraclinoid Aneurysms: A Systematic Review and Meta‐Analysis - Nagheli Fernanda Borjas‐Calderón; Aaron Rodriguez‐Calienes; J. Pierre Zila‐Velasque; Pamela Grados‐Espinoza; Fernando Terry‐Escalante; Marco Malaga; Juan Vivanco‐Suarez; Sandra Chavez‐Malpartida; Cristian Moran‐Mariños; Santiago Ortega‐Gutierrez (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Paraclinoid aneurysms (PAs) have traditionally been treated with clipping. However, with the emergence of new techniques, endovascular treatment (EVT) has supplanted surgical treatment in recent years. We aimed to determine the safety and efficacy of EVT and microsurgical clipping for PAs. Methods A systematic review was performed in Scopus, Embase, Medline, Web of Science, and Cochrane from inception to March 2022 for all studies that tested the safety and efficacy of EVT or microsurgical clipping of PAs. Efficacy outcomes included complete aneurysm occlusion at last follow‐up, immediate complete occlusion, and an mRS 0–2 at last follow‐up. Safety outcomes included mortality, intraoperative and postoperative complications. We performed a random‐effects meta‐analysis of proportions and assessed the statistical heterogeneity across studies with I2 statistics. Results Eighty‐nine studies included 6496 patients, 3682 treated with EVT and 2814 with microsurgical clipping. Immediate complete occlusion rates were 92% (95% CI 88 – 96%; I2 = 60%) and 46% (95% CI 34 – 59%; I2 = 93%) for clipping and EVT, respectively. The rate of complete occlusion at last follow‐up was 94% (95% CI 91 – 96%; I2 = 0%) and 69% (95% CI 63 – 74%; I2 = 79%) for microsurgical clipping and EVT, respectively. Among EVT studies, the rate of complete occlusion was 54% (95% CI 48 – 59%; I2 = 50%), 52% (95% CI 39 – 64%; I2 = 73%), and 77% (95% CI 54 – 91%; I2 = 91%) for primary coiling, stent‐assisted coiling, and flow diversion, respectively. Among clipping studies, the rate of last follow‐up mRS 0–2 was 86% (95% CI 76 – 92%; I2 = 72%). Among EVT studies, the rate of last follow‐up mRS 0–2 was 94% (95% CI 86 – 98%; I2 = 93%). Mortality rate was 4% (95% CI 3 – 7%; I2 = 57%) and 1% (95% CI 0 – 3%; I2 = 0%) for clipping and EVT, respectively. Among EVT studies, the mortality rate was 3% (95% CI 1 – 6%; I2 = 0%) and 3% (95% CI 1 – 9%; I2 = 39%) for primary coiling and flow diversion, respectively. Intraoperative and postoperative complications were present in 9% (95% CI 6 – 14%; I2 = 68%) and 21% (95% CI 17 – 26%; I2 = 87%) among clipping studies, respectively. Intraoperative and postoperative complications were present in 6% (95% CI 4 – 9%; I2 = 64%) and 9% (95% CI 6 – 13%; I2 = 72%) among EVT studies, respectively. Conclusions In conclusion, microsurgical clipping and EVT for PAs are both safe and effective treatment modalities. Treatment via either approach should be determined on a case‐by‐case basis and according to institutional experience and resources.